2008
DOI: 10.1074/jbc.m804869200
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structure of the N-terminal Coiled Coil Domain of the Andes Hantavirus Nucleocapsid Protein

Abstract: The hantaviruses are emerging infectious viruses that in humans can cause a cardiopulmonary syndrome or a hemorrhagic fever with renal syndrome. The nucleocapsid (N) is the most abundant viral protein, and during viral assembly, the N protein forms trimers and packages the viral RNA genome. Here, we report the NMR structure of the N-terminal domain (residues 1-74, called N 1-74 ) of the Andes hantavirus N protein. N 1-74 forms two long helices (␣ 1 and ␣ 2 ) that intertwine into a coiled coil domain. The conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Previous results revealed that hantavirus NP undergoes trimerization (34,35) and that NP trimers specifically recognize a conserved panhandle structure that is formed by the complementary base pairing of the 5= and 3= ends of the hantaviral genome (36,37). Further results showed that the N-terminal domains of the ANDV (38) and SNV NPs (34) possess a coiled-coil architecture that is comprised of two antiparallel helices stabilized by conserved hydrophobic residues, while the C-terminal domain (residues 370 to 429) forms two helices; both domains are essential for NP oligomerization (35).…”
mentioning
confidence: 63%
“…Previous results revealed that hantavirus NP undergoes trimerization (34,35) and that NP trimers specifically recognize a conserved panhandle structure that is formed by the complementary base pairing of the 5= and 3= ends of the hantaviral genome (36,37). Further results showed that the N-terminal domains of the ANDV (38) and SNV NPs (34) possess a coiled-coil architecture that is comprised of two antiparallel helices stabilized by conserved hydrophobic residues, while the C-terminal domain (residues 370 to 429) forms two helices; both domains are essential for NP oligomerization (35).…”
mentioning
confidence: 63%
“…Coiled coils have been shown to be important for self-interaction of hantavirus nucleoprotein (2)(3)(4)63). Nevertheless, the contribution of additional sequences that stabilize homotypic interactions has also been reported (28,29).…”
Section: Discussionmentioning
confidence: 98%
“…This shows that the N protein is involved in, and therefore potentially can interfere with, several cellular functions. The secondary structure of the first 70 amino acids in the N protein has been solved (3,6,52). From these reports, it has been suggested that PUUV N-protein D27 is located within ␣-helix 1, while D35 is on the apex formed between ␣-helix 1 and ␣-helix 2.…”
Section: Discussionmentioning
confidence: 98%